2014
DOI: 10.1002/jat.3001
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylarsinic acid (DMAV) changed the expressions of proliferative related factors and secretion of inflammatory cytokines in rat bladder

Abstract: Dimethylarsinic acid (DMA(V) ), the major urinary metabolite of inorganic arsenic, is a urinary bladder carcinogen and bladder tumor promoter in adult rats. Increased urothelial cellular proliferation has been considered as an earlier phenotype in DMA(V) -induced bladder carcinogenesis. The present study examined the ultrastructural changes of bladder epithelial cells and expressions of proliferation factors, as well as the secretion of inflammatory cytokines in rats exposed to DMA(V) for 10 weeks by transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…In our previous study, 200 ppm DMA V treated rats exhibited significantly increased inflammatory factor TGF- β 1 level in urine compared to the control rats [ 5 ]. In the present immunohistochemical localization analysis, TGF- β expression was elevated in 100 and 200 ppm DMA V treated rat bladder epithelium.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study, 200 ppm DMA V treated rats exhibited significantly increased inflammatory factor TGF- β 1 level in urine compared to the control rats [ 5 ]. In the present immunohistochemical localization analysis, TGF- β expression was elevated in 100 and 200 ppm DMA V treated rat bladder epithelium.…”
Section: Resultsmentioning
confidence: 99%
“…Our precious study found DMA elevated expressions of proliferation factors, such as PCNA, cyclin D1, and COX-2, in bladder epithelium [ 5 ]. The possible mechanism of DMA V on bladder epithelium in this study was speculated because DMA V activated NF- κ B signal pathway, which increased the secretion of TGF- β and IL-1 β in rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, arsenical herbicides were extensively used in the US and elsewhere. Dimethylarsinic acid (DMA), the major urinary metabolite of inorganic arsenic, is a urinary bladder carcinogen that increased TGF-β secretion in rat urine [136]. A separate study found that DMA induced EMT through several mechanisms including upregulation of HER2 that is also known to increase TGF-β [137].…”
Section: Role Of Pesticides In Emt and Metastasismentioning
confidence: 99%